Risk factors for re-hospitalization within 90 days of discharge for severe influenza in children - Shuo Yang; Sukun Lu; Can Qi; Yinghui Guo; Le Wang (BMC Infectious Diseases)
Abstract Background Influenza virus is a contagious respiratory pathogen that can cause severe acute infections with long-term adverse outcomes. For paediatric patients at high risk of severe influenza, the readmission and the associated risk factors remain unclear. Methods Children discharged with a diagnosis of severe or critical influenza from October 2021 to March 2022 were included. The disease severity was categorized according to the “2020 edition of the Chinese expert consensus on the diagnosis and treatment of influenza in children”. Demographic data, clinical characteristics, underlying medical conditions, microbiology, treatment outcomes, and 90-day readmissions were retrieved and retrospectively analyzed. Those who tested positive for COVID-19 were excluded. Risk factors independently associated with readmission were identified using multiple logistic regression models. Results During the study period, 225 children with severe influenza were hospitalized and 14.7% (33/225) of them were readmitted within 90 days. The median length of readmission was 62 (IQR, 31–76) days, and the most common cause of readmission was pneumonia. M. pneumoniae and influenza virus are the most common infections for readmission The children who were readmitted were more likely to have critical influenza and neurological comorbidities compared to patients without readmission. The readmitted children had a significantly higher proportion of natural killer cells and a shorter febrile duration and length of stay on their first admission, compared with those who were not readmitted. Rhinosinusitis (OR = 30.085, p = .008) and high level of natural killer cells (OR = 1.107, p = .012) were independent risk factors and febrile duration (OR, 0.748, p = .018) was a protective factor for 90-day readmission. Conclusions Our findings suggest that, to reduce the potential readmission of children with severe influenza, a sustained focus on the risk factors including rhinosinusitis and over-activated host immune response during the index hospitalization is needed.